Analisis Faktor-faktor yang Memengaruhi Keberhasilan Koperasi Sektor Pertanian di Provinsi Lampung - Rahayu, Sari; Lestari, Dyah Aring Hepiana; Rosanti, Novi (Politeknik Negeri Lampung., 2023)
Cooperatives can potentially have a broad impact on the economic order. The success of cooperatives can benefit members, the surrounding environment, and even the broader scope. The agricultural sector is the third largest number of cooperatives in Lampung Province. This research aimed to analyze the factors that affect cooperative business volume, and net income (SHU) of agricultural sector cooperatives in Lampung Province. The number of samples in this study was 33 cooperatives. The samples are cooperatives that run agricultural related businesses and cooperatives whose members are agricultural business actors in Lampung Province. The multiple linear regression was used to analyze factors that influenced the business volume and the net income (SHU). It was found the number of members and business units have a negative effect on business volume, while capital and loan capital have a positive effect on business volume. At the same time, the variables of managers' availability and the chairman's education level do not affect the business volume of agricultural sector cooperatives in Lampung Province. Self-capital, loan capital, and the chairman's high level of education have a positive effect on business rest, and the number of members and business units have a negative effect on the net income (SHU). In contrast, the manager availability and the chairman’s education level at imtermediate and low levels have no effect on the net income (SHU) of agricultural sector cooperatives in Lampung Province. Keywords: agricultural cooperatives, business volume, net income (SHU)